STUDIES ON INDUCTION OF OESTRUS IN POST-PARTUM ANOESTRUS LOCAL COWS WITH PROGESTERONE PRIMED GnRH AND PROGESTERONE TREATMENT - KASBE, R D; MARKANDEYA, N M; SAWALE, A G; PAWAR, S A (The Indian Journal of Animal Reproduction, 2023)
The local anoestrus cows were treated for induction of oestrus and out of eighteen treated cows withinjection progesterone (250 mg) on day1followed by inj. GnRH (0.0105 mg) on day 1 O in group I, 88.88 per centanimals exhibited oestrus and after insemination 81.25 per cent cows conceived with 1. 76 services per conception,whereas in group II (n = 18) of Progesterone treatment 63.63 per cent cows showed exhibitory oestrus and afterinsemination, 63.63 per cent conceived with 2.00 services per conception as against control. The progesteronetreatment response in terms of oestrus induction,conceptions, pregnancy rate and cyclicity rate statisticallydiffered with progesterone primed GnRH therapy.
Keywords: POST-PARTUM; PROGESTERONE PRIMED; GnRH